Pengaruh Tingkat Inflasi,PDRB,Suku Bunga Kredit,Serta Kurs Dollar Terhadap Investasi - Marsela, Ni Made Krisna (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2014)
Investment is an important component in helped economic growth. Some macroeconomic variables such as inflation, GDP, interest rates, and exchanged rate  considered by investor to invest in a region. This study aims to determined the effect of the inflation rate, GDP, interest rates, and dollar exchange rate against of investment in the Province of Bali . In this research used multiple linear regression analysis and for the validity test of data used stationerity test, cointegration test, and error correction mechanism (ECM). The results showed that the GDP variable had positive and significant effect on investment in the Province of Bali . Dollar exchange rate variable has a negative and significant effect on the amount of investment in the Province of Bali. In this research the variable rate of inflation and interest rates did not significantly influence the amount of investment in the province of Bali .
Keywords: Investment; Inflation; GDP; Exchange Rate